2020
DOI: 10.1016/j.ajog.2020.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing surgical blood loss at cesarean hysterectomy for placenta previa with evidence of placenta increta or placenta percreta: the state of play in 2020

Abstract: The evolution of multidisciplinary team-based care for women with placenta accreta spectrum (PAS) disorder has delivered step-wise improvements in clinical outcomes. Central to this overall goal is the ability to limit blood loss at surgery. Placement of inflatable balloons within the pelvic arteries, most commonly in the anterior divisions of the internal iliac arteries, became popular in many centers, at the expense of prolonging surgical care, and with attendant risks of vascular injury. In tandem, the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 43 publications
(33 reference statements)
3
66
0
3
Order By: Relevance
“…shows that women with a history of caesarean delivery have the highest risk of developing placenta accreta [36][37][38]. In the present study, we found a signi cant positive association between previous cesarean section history and the incidence of placenta accreta.…”
Section: Discussionsupporting
confidence: 67%
“…shows that women with a history of caesarean delivery have the highest risk of developing placenta accreta [36][37][38]. In the present study, we found a signi cant positive association between previous cesarean section history and the incidence of placenta accreta.…”
Section: Discussionsupporting
confidence: 67%
“…There are parallels between the increasing number of caesarean section cases and the increasing incidence of placenta accreta [34,35]. Evidence shows that women with a history of caesarean delivery have the highest risk of developing placenta accreta [36][37][38]. In the present study, we found a signi cant positive association between previous cesarean section history and the incidence of placenta accreta.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, preparations should have been made to reduce the risk of injury and to prevent uncontrolled bleeding or incomplete resection. Therefore, we performed abdominal aortic balloon catheter placement before surgery [27].…”
Section: Discussionmentioning
confidence: 99%